The Influence of Threats and Protective Co-creation Behavior on Active Online Banking Customer Loyalty with Social Support Moderation - Himalia, Ika; Sutarso, Yudi (At-Tadbir : jurnal ilmiah manajemen, 2025)
This study investigates the influence of threat assessment and protection co-creation behavior on the loyalty of active online banking customers, with social support acting as a moderating variable. The research utilized a survey method, collecting data from 96 active customers of Indonesia's four largest banks—BCA, BRI, BNI, and Mandiri—located in Surabaya, Sidoarjo, Gresik, Lamongan, Bangkalan, Mojokerto, and DKI Jakarta. Hypothesis testing was conducted using Partial Least Squares - Structural Equation Modeling (PLS-SEM). The findings reveal that threat assessment positively influences protection co-creation behavior, and protection co-creation behavior positively influences loyalty. Contrary to expectations, perceived threats also have a direct positive effect on loyalty. Additionally, social support significantly moderates the relationship between threats and protection co-creation behavior. This study offers valuable insights for banking management to enhance customer loyalty by improving risk management, fostering protection co-creation behavior, and strengthening social support mechanisms.